Violence against women: what everyone needs to know® - True, Jacqui (What everyone needs to know, 2021)
Eliminating violence against women globally is now seen as one of the major challenges of the twenty-first century. This book introduces a wide readership to the problem of violence against women and girls (VAWG) identified by social movements, researchers, and policymakers. It provides raw material, stories from around the world, macro data, and up-to-date knowledge on the various forms of VAWG. It highlights the intersections of VAWG with several other issues, and sets out the most promising policy and advocacy frameworks to end this violence.